Productivity, cost, and profitability of kale produced in a low tunnel - da Silva Ponce, Franciely; de Lima Toledo, Claudia Aparecida; Gawski Casagrande, Jéssica; Grzebieluckas, Cleci; Roggia Zanuzo, Márcio; Seabra Júnior, Santino (Comunicata Scientiae, 2022)
This study evaluated the productivity and profitability of kale hybrids cultivated either in a low tunnel or an open field. The study was conducted using two hybrids of Hi-crop and Kobe kale and six environments: low tunnels covered with agrotextiles at a weight of 15 g.m-2, white organza at a weight of 47 g.m-2, 35% red screen, 35% thermo-reflective screen, 35% black screen, or an open field, with four repetitions. The total operating cost and economic indicators related to the cultivation of each hybrid and environment were calculated by estimating the operating profit, profitability index (%), gross margin (%), and leveling points (kg.h-1 and price. pack-1). Both hybrids showed high productivity and profitability indices in all environments. The hybrid ‘Hi-crop’ showed the highest productivity when cultivated under the organza tunnel, with a 26% greater value than that in the open field. The use of a protected environment reduced the need for insecticides, which was reflected in productivity and, consequently, in the profitability of the crops.